The doctrine of creation ; part 1 - Barth, Karl, 1885-1964; Bromiley, Geoffrey William; Torrance, Thomas Forsyth, 1913- (Edinburgh, Scotland T and T Clark, 1962)
Includes indexes.
Original German ed. : Die Kirchliche Dogmatik, II : Die Lehre von der Schopfung, 1
Keywords: Creation -- biblical teaching